Inverse Halogen Bonds Intermolecular Interactions (Journal of Atomic and Molecular Sciences, 2011)
A new number of inverse halogen bonds (IXBs) intermolecular interaction system of $Y-F...DB_2 (D=C, N, O$ or $S; B=O$ and $S; Y=Cl$) have been investigated at B3LYP/6-311++$g(d, p)$ computational level. According to the BSSE corrected interaction energy, it can be concluded that the stability of the five IXBs complexes of the $ClF...DB_2$ system increases in the order of $ClF...CS_2 < ClF...CO_2 < ClF...NO_2 < ClF...O_3 < ClF...SO_2.$ Comparing the $ClF$ monomer with ClF moiety of the complexes, the chemical shifts of F atoms all increased by a certain degree and presented a trend to downfield. This indicates that the electrons flow from $ClF$ to $DB_2 (D=C, N, O$ or $S; B=O$ or $S$) and the IXBs form between $ClF$ and $DB_2.$